Konsultasi Katarak Dengan Prosedur Certainty Factor - Naiborhu, Rinda Anisa; Agus, Raja Tama Andri; Mardalius, Mardalius (Jurnal Algoritma, 2025)
Cataract is one of the main causes of visual impairment, especially in the elderly, and requires a quick and accurate diagnosis to prevent further complications. To support the diagnosis process, a web-based expert system with the Certainty Factor (CF) method was developed that is able to calculate the certainty level of diagnosis based on the symptoms experienced by the patient. The system was built using the PHP programming language and MySQL database, with a waterfall development model. Testing was conducted on 50 patient data that had been validated by an ophthalmologist. The evaluation results showed that the system accuracy rate reached 92%, with 46 out of 50 diagnoses in accordance with the results of manual medical examinations. The system is not only able to provide diagnosis recommendations quickly and efficiently, but also improve the accuracy of initial medical decision-making. The practical implication of this research is to increase the efficiency of health services, especially in facilities with limited specialists, and provide convenience for patients in obtaining initial information related to cataract conditions. This application has the potential to be a supporting solution in the digital transformation of health services in the field of eye health.